IMPROVING THE EFFICIENCY OF REGIONAL FOOD INDUSTRY ENTERPRISES - Khodjamov , Jamshid Toxtamurodovich (THE INNOVATION ECONOMY, 2026)
This article examines the issues of improving the economic efficiency of regional food industry enterprises. The study analyzed the activities of food industry enterprises in selected regions of Uzbekistan during 2019–2024. A systematic approach was applied based on the IMRAD (Introduction, Methods, Results, and Discussion) scientific writing standard. The main efficiency indicators of regional food industry enterprises were assessed using correlation-regression analysis, SWOT analysis, cluster analysis, and expert survey methods. The results show that technological modernization, diversification of the raw material base, and human resource development are the most important factors of enterprise efficiency. Based on the research findings, practical recommendations aimed at improving the efficiency of regional food industry enterprises were developed.